FORMATION OF MOTOR CULTURE OF STUDENTS IN THE LESSONS OF RHYTHMIC GYMNASTICS - Khaitbayeva Barnokhon Bakhodirovna; Ruzieva Makhliyo Kayumovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article shows the theoretical substantiation and practical development of the pedagogical system for the formation of students' motor culture by means of rhythmic gymnastics.